Analysis of the Effectiveness of the KUR Loan Program at Bank Rakyat Indonesia (BRI) Unit Jatipurno in Developing SMEs in the Jeporo Area of Wonogiri Regency for the Years 2021-2022 - Tias, Zela Amalia Rahayuning; Rohmah, Wafrotur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The government has appointed BRI to distribute KUR (People’s Business Credit) to expand access to financing for MSMEs. This initiative supports people-based economic empowerment programs. Consequently, the government must also assist MSMEs through its policies to enhance the welfare of small entrepreneurs. This research employs a qualitative phenomenological approach, utilizing three primary methods: interviews, observation, and documentation. The interview method involves face-to-face meetings between the researcher and selected informants. The data analysis employs the interactive model from Miles and Huberman, involving interactive and continuous activities until data saturation is achieved. The findings of this research indicate that the effectiveness and impact of the KUR program at the Jatipurno unit of Bank Rakyat Indonesia (BRI) on MSME development in Jeporo are as follows: The KUR program has successfully increased access to capital for those in need, effectively boosting production capacity, expanding markets, and increasing income in Jeporo. Support from the local government and training provided by BRI have also contributed to the program's success. Despite challenges such as a lack of understanding of financial management and complicated bureaucracy, the KUR program at the BRI Jatipurno unit has significantly impacted the growth and development of MSMEs in Jeporo.